2016
DOI: 10.1002/cctc.201600624
|View full text |Cite|
|
Sign up to set email alerts
|

Molybdenum Imido Alkylidene N‐Heterocyclic Carbene Complexes: Structure–Productivity Correlations and Mechanistic Insights

Abstract: The syntheses and single‐crystal X‐ray structures of a series of Mo–imido alkylidene N‐heterocyclic carbene (NHC) complexes (1–15) and of the first complexes containing bidentate NHC‐phenolate ligands (16–18) are reported. Mo(N‐2,6‐Me2‐C6H3)((1‐R‐phenethyl)‐3‐mesitylimidazolidin‐2‐ylidene)(CHR)(OTf)2 (R=CMe2Ph, 1) is the first enantiomerically pure Mo–imido alkylidene NHC catalyst. With [Mo(N‐2,6‐Me2‐C6H3)(IMes)(CHR)(CH3CN)(OTf)(CH3CN)+ B(ArF)4−] (7), turnover numbers up to 545 000 were achieved in the homomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
98
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 40 publications
3
98
1
Order By: Relevance
“…Also, as anticipated, I5 , with the electron‐withdrawing chloro‐substituents at the aromatic imido ligand, displays the highest T exo,max =186 °C and T onset =115 °C of all screened bistriflate catalysts. In addition, T onset for I2 – I4 also correlates with their previously published coalescence temperature T c =60 °C ( I4 ), T c =79 °C ( I2 ) and T c =85 °C ( I3 ) (previously measured in deuterated 1,2‐dichlorobenzene, Table ). Poly(DCPD) derived from the polymerization with catalysts I1 ( T= 110 °C), I3 ( T= 110 °C) and I4 ( T= 80 °C) showed swelling in toluene of 25, 45 and 50 %, whereas poly(DCPD) polymerized by I2 ( T= 80 °C) and I5 ( T= 150 °C) showed no swelling at all, indicating high crosslinking (Table S13, S.I.).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Also, as anticipated, I5 , with the electron‐withdrawing chloro‐substituents at the aromatic imido ligand, displays the highest T exo,max =186 °C and T onset =115 °C of all screened bistriflate catalysts. In addition, T onset for I2 – I4 also correlates with their previously published coalescence temperature T c =60 °C ( I4 ), T c =79 °C ( I2 ) and T c =85 °C ( I3 ) (previously measured in deuterated 1,2‐dichlorobenzene, Table ). Poly(DCPD) derived from the polymerization with catalysts I1 ( T= 110 °C), I3 ( T= 110 °C) and I4 ( T= 80 °C) showed swelling in toluene of 25, 45 and 50 %, whereas poly(DCPD) polymerized by I2 ( T= 80 °C) and I5 ( T= 150 °C) showed no swelling at all, indicating high crosslinking (Table S13, S.I.).…”
Section: Resultssupporting
confidence: 85%
“…I2 adopts a distorted square pyramidal (SP) structure ( τ =0.325) in which one triflate ligand is coordinated trans to the NHC (Mo−O4, 216.97(17) pm, Figure ). I2 and I3 , I4 as well as I5 , which also show a distorted SP structure, display comparable bond lengths, angles and geometry in the solid state. For I2 , I3 and I5 the longest Mo‐OTf bond is coordinated trans to the NHC, whereas for I4 the longest Mo‐OTf bond is situated trans to the imido ligand (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We already have shown that cationic molybdenum imido alkylidene NHC complexes are highly active catalysts in various olefin metathesis reactions . Here we prepared a wide range of complexes with the general formula [Mo( N R′)(CHCMe 2 R)(NHC)(X)][B(Ar F ) 4 ] (Figure , X=anionic ligand).…”
Section: Resultsmentioning
confidence: 99%
“…Addition of one equivalent of lithium pentafluorophenoxide to 3 resulted in the quantitative exchange of the betaine but not the triflate ligand by pentafluorophenoxide yielding [Mo{ N ‐2,6‐(Me 2 )C 6 H 3 }(CHCMe 2 Ph)(IMesH 2 )(OTf)(OC 6 F 5 )] ( 4 ) ).…”
Section: Resultsmentioning
confidence: 99%